고교생들에 대한 금연교육 효과 - 김택민 (연세대학교 보건대학원, 1990)
[한글] 일부 중소도시에 위치한 고등학교 남학생들의 흡연율과 흡연의 해독성에 대한 지식수준을 파악하고 금연교육이 학생들의 흡연에 미치는 단기적인 영향을 측정하고자 본 연구가 시행되었다. 연구대상은 강원도 원주시 소재 2개 남자 고등학교 일학년 학생들이였으며 금연교육내용은 40분간에 걸친 흡연의 위해성 시범 그리고 20분간에 걸친 비디오를 통한 교육으로 구성되어 있다. 1988년 5월 실험군 323명과 비교군 383명에 대하여 금연 교육전 흡연율을 조사한후 실험군에 대하여 금연교육을 실시하고 일년후인 1989년 동일한 조사표를 이용 양군에서 흡연율 등을 재조사하여 금연교육의 흡연에 주는 영향을 분석하였다. 금연교육의 흡연에 주는 영향은 조비차비와 다변수로지스틱분석을 통한 비차비로 분석하였다. 1. 교육전 실험군과 비교군의 흡연율은 각각 9.7%, 7.8%이었고 교육후에는 각각 31.2%와 22.1%로 증가하였다. 2. 교육전 실험군과 비교군의 흡연지식점수는 각각 4.6점과 5.4점이었고 교육후에는 각각 5.5점과 5.2점으로 실험군에서만 유의하게 증가하였다. 3. 흡연에 영향을 주는 변수의 조비차비는 종교가 기독교가 아닌 경우 1.7(p<0.05), 동생의 흡연을 말리지 않겠다는 군에서 2.6(p<0.01), 부모가 흡연하는 경우 1.1(p>0.05),금연교육을 받은군 1.6(p<0.01), 자가 이외에서 거주하는 경우 1.2(p>0.05)였다. 4. 교육후 흡연영향 변수의 다변수로지스틱분석결과 종교가 기독교가 아닌 경우, 동생의 흡연을 말리지 않겠다는 경우, 부모가 흡연하는 경우, 그리고 흡연교육을 받은 군에서 비차비가 각각 1.3(p>0.05), 1.6(p<0.05), 1.8(p>0.05), 1.2(p>0.05)이었다. 그러나 흡연교육유무는 통계학적으로 유의하지 않았다. 이상의 결과를 종합하면 일부 남자고등학교 일학년 학생에 대한 단기적인 금연교육의흡연예방효과는 이 연구의 표본수를 가지고는 통계학적으로 유의한 결과를 관찰할 수 없었으며 앞으로의 금연교육의 효과를 보는 연구에서는 충분한 표본수가 필요하고 실험군,비교군의 선정에 흡연에 영향을 주는 변수의 세심한 감안이 필요하며 가능한 실험대상의연령을 낮추고 아울러 관찰기간을 흡연시작이 많이 일어나는 시기까지 연장할 것이며 이기간동안 반복적인 금연교육을 하는 것이 바람직하다고 생각된다. [영문] In order to examine the effect of an anti-smoking education method on smoking, a before-and after-survey were conducted with a self-completing questionnaire in 1988 and 1989. A total of 323 students from one high school and 383 students from the other high school in Wonju were selected as an experiment and comparison group respectively. The anti-smoking education was proceeded with a forty-minute-demonstration about danger of smoking and a twenty-minute-long video education. The results were as follows: 1. Before the education, the smoking rate of the experiment group and comparison group showed as 9.7% and 7.8% respectively. after one year of education their smoking rates increase to 31.2% and 22.1% respectively. 2. Before the education the smoking knowledge score of experiment group was 4.6 and that of comparison group was 5.4. After the education they were showed 5.2 and 5.5 respectively showing a statistically significant increase only in experiment group. 3. The crude odds ratio of smoking for non-Christian was 1.7(p<0.05), that for those who would allow brother's smoking 2.6(p<0.01), for those who have smoking parents 1.1(p>0.5), 1.2 for who don't live with their parents(p>0.5), and 1.6 for those who take anti-smoking education(p<0.01). 4. An unconditional logistic regression model estimates the controlled odds ratios of smoking for non-Christian 1.3(p<0.05), 1.6 for those who would allow brothers' smoking(p<0.05), 1.8 for those who have smoking parents(p>0.05), and 1.2 for those who took the anti-smoking education(p>0.05). It is concluded that a short-term anti-smoking education increases the knowlege of harmful effects of smoking but it is also shown that the education can not show statistically significant effect on smoking itself with 706 sample size studied in this study.
보건학과/석사